Effectiveness of an exercise program on range of motion, strength, and lumbopelvic stability in Division I collegiate baseball players - Meggs, S.; Plummer, H. A.; Diaz, P.; Chien, A.; Michener, L. A. (Journal of Athletic Training, 2019)
Context: Deficits in shoulder range of motion (ROM), strength, and lumbopelvic stability are associated with risk of arm injury in baseball players. The purpose of this study was to assess the effects of a standardized exercise program on shoulder ROM, shoulder and hip strength and lumbopelvic stability over the course of a playing season in collegiate baseball players. Methods: This was a prospective cohort study performed in the athletic training room of Division I baseball players (n = 43; age = 19.6 ± 1.2 years; height = 185.8±5.5cm; weight = 90.5 ± 7.0 kg).Data were collected prior to and following the season.Passive shoul-der IR, ER, and horizontal adduction ROM was measured with an inclinometer. Shoulder IR and ER strength was measured with a hand-held dynamometer with the arm at the side. Hip abduction strength was measured with a hand-held dynamometer in sidelying. For all strength measures, two maxi-mal isometric contraction trials were performed on each extremity, and the average used for analysis. Lumbopelvic stability of the lead leg (contralateral to throwing arm) was assessed dynamically using a single-leg step-down (SLSD) task in which participants stood on their lead leg and lowered to the floor from an 8'' step. Participants performed a strengthening, stability, and stretching program three times a week for four months over the course of the season. Shoulder IR and ER strengthening exercises targeted those respective muscles. Shoulder stretching exercises were aimed at improving IR, ER, and horizontal adduction. Dynamic core exercises targeted a stable trunk position with upper or lower extremity movement. Hip strengthening exercises targeted the gluteals. Static core exercises required use of the abdominal muscles to stabilize the spine isometrically. Paired samples t-tests were performed to compare pre-season to post-season outcome measures. Results: Data are presented in Table 1.From pre-season to post-season, there were significant increases in hip abduction strength (Mean Difference= 11.1Nm; p=0.015), horizontal adduction ROM (Mean Difference= 6.1°; p<0.01), shoulder IR strength (Mean Difference= 1.4kg; p=0.046). ER strength significantly de-creased over the course of the season (Mean Difference= -1.1kg; p=0.004). There were no significant changes in lumbopelvic stability as measured by trunk lean, trunk flexion and pelvic drop during the SLSD task; or in IR or ER ROM. Conclusions: The exercise program was effective in improving horizontal adduction ROM, shoulder IR strength, and hip abduction torque of the lead leg. The lack of change in IR and ER ROM and lumbopelvic stability with the intervention, maybe related to the lack of deficits at the start of the season. Alternatively, the dosing and duration of the program may not have been adequate to elicit change. Future studies need to determine if changes in strength and ROM found in this study are related to decreased injuries, to demonstrate the value in reducing injury risk Context: Unilateral anterior knee pain (AKP) may cause bilateral quadriceps weakness and inhibition. However, it is unclear how unilateral AKP affects bilateral quadriceps endurance and hip joint flexibility. We examined if patients with unilateral AKP present bilateral deficits in quadriceps neuromuscular function and hip joint flexibility when comparing with the matched healthy knees. Methods: Study design: Cross-sectional study. Setting: Laboratory. Patient population: Twenty-three patients with unilateral AKP (8 females,15 males; age: 22.0 ± 1.2 years, height: 171.7 ± 2.9 cm, mass: 70.6 ± 7.5 kg, body mass index: 23.8 ± 1.9 kg/m2, time since pain: 46.5 ± 15.0 months) and 23 matched healthy controls (8 females, 15 males; age: 22.7 ± 1.3 years, height: 171.0 ± 3.0 cm, mass: 70.8 ± 5.6 kg, body mass index: 24.1 ± 1.5 kg/m2). Outcome measures: Pain perception using visual analog scale (cm), functional outcomes using the Lower Extremity Functional Scale (score), and knee joint effusion (sum of the circumferences of the superior and inferior pole of patella in cm) were obtained. Quadriceps neuromuscular function was assessed by strength (isometric in N·m/kg), endurance (isokinetic at 180°/s in N·m/kg), and voluntary activation (central activation ratio). Hip joint flexibility was measured by single straight leg raise and modified Thomas test (°). Statistical analyses: Parametric or a non-parametric tests (P < .05) with calculations of Cohen's d effect size with 95% confidence intervals were performed. Results: Knee joint circumference was not different, indicating that our AKP patients did not have joint effusion (P = .28). As compared with the matched healthy controls, patients with unilaterall AKP showed (1) a greater pain perception (0.0 ± 0.0 versus 4.3 ± 0.7 cm, P < .0001, d = 3.50); (2) a lower score on functional outcomes (79.6 ± 0.3 versus 56.3 ± 4.6 score, P < .0001, d = 1.20); and (3) a less quadriceps strength (3.5 ± 0.2 versus 2.8 ± 0.2 N·m/kg, P < .0001, d = 1.15), endurance (peak torque: 1.65 ± 0.07 versus 1.51 ± 0.05 N·m/kg, P = .02, d = 0.65; total work: 76.5 ± 3.0 versus 69.6 ± 2.3 N·m/kg, P = .01, d = 0.75), and voluntary activation (0.95 ± 0.02 versus 0.83 ± 0.03, P < .0001, d = 1.41), and hip joint flexibility (flexion: 86.7 ± 4.6 versus 72.5 ± 4.3°, P = .001, d = 0.92; extension: 11.9 ± 1.4 versus 7.8 ± 2.3°, P = .03, d = 0.64). Conclusions: Our data suggest that unilateral AKP, without the absence of joint effusion, results in bilateral deficits in quadriceps neuromuscular function and hip joint flexibility. Since chronic AKP may cause bilateral symptoms, clinicians should consider restoration of both neuromuscular function and the joint flexibility along with pain reduction.